Fenghuangor imperator gen. et sp. nov. of Fulgoridiidae from the Middle Jurassic of Daohugou Biota (Hemiptera: Fulgoromorpha) - Li, Shu; Szwedo, Jacek; Ren, Dong; Pang, Hong (Zootaxa, 2011)
A new genus of giant Fulgoridiidae, Fenghuangor imperator gen. et sp. n., from the Middle Jurassic Biota of Daohugou, Inner Mongolia, North-East China is described. Its characters are discussed as well as family features in respect to new findings from the Jurassic.